1995
DOI: 10.2466/pr0.1995.76.3.915
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Salespersons' Influence and Consumers' Shopping Orientations

Abstract: Realizing the scarcity of research into consumers' susceptibility to salespersons' influence, this concept is developed as a general personality trait and unidimensional construct. Its associations with the two primary shopping orientations, recreational and economic, were explored. Analysis indicates that, while consumers' susceptibility to salespersons' influence and recreational shopping appear to be related, no such evidence emerged for economic shopping. These findings, as well as their various implicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Salespeople play a key role in the purchasing process by informing customers about available options and then helping them decide which option is best (Wilkie 1986). A stream of literature has examined customers' attitudes about salespeople in high-involvement decision-making, or consumer susceptibility to salesperson influence (Goff and Walters 1995). A retailer's salespeople are a valuable source of information; salesperson expertise is a source of expert power affecting persuasion and attitude change; and salespeople can convince consumers to accept information that is compatible with closing the sale (Goff, Bellenger, and Stojack 1994).…”
Section: Sales Force Recommendationmentioning
confidence: 99%
“…Salespeople play a key role in the purchasing process by informing customers about available options and then helping them decide which option is best (Wilkie 1986). A stream of literature has examined customers' attitudes about salespeople in high-involvement decision-making, or consumer susceptibility to salesperson influence (Goff and Walters 1995). A retailer's salespeople are a valuable source of information; salesperson expertise is a source of expert power affecting persuasion and attitude change; and salespeople can convince consumers to accept information that is compatible with closing the sale (Goff, Bellenger, and Stojack 1994).…”
Section: Sales Force Recommendationmentioning
confidence: 99%
“…The overall model accounted for 25% of the variance in consumers' susceptibility to salespersons' influence. Goff and Walters (1995) proposed an investigation of the relationship between consumers' susceptibility to salespersons' influence and various other susceptibilities to influence for possible common psychology origins. This study identified interdependent self-construal as a common psychological origin, and tested propositions that link interdependent self-construal with consumer's susceptibility to salespersons' influence via a group of mediating variables, including public self-consciousness, susceptibility to interpersonal influence, and susceptibility to store atmosphere influence.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Individuals with this interdependent view of the self tend to think and behave in ways that emphasize their connectedness to others and that strengthen existing relationships (Cross et al, 2000). Shoppers with strong needs for affiliation might be motivated by their desire to bolster their self-image through reference identification with other shoppers or salespersons (Goff and Walters, 1995). Thus it can be expected that interdependent self-construal is positively related to consumers' susceptibility to interpersonal influence, and consumers' susceptibility to salespersons' influence.…”
Section: Interdependent Self-construalmentioning
confidence: 95%
See 2 more Smart Citations